2005
DOI: 10.1080/07315724.2005.10719445
|View full text |Cite
|
Sign up to set email alerts
|

Diet Quality in Young Children Is Influenced by Beverage Consumption

Abstract: Dairy foods remain an important source of calcium and vitamin D, while added sugar beverages and, to a lesser extent, 100% juice decrease diet quality of young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
89
2
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(102 citation statements)
references
References 24 publications
8
89
2
3
Order By: Relevance
“…Interestingly, children who were overweight/obese at baseline but had acceptable BMI at follow-up consumed significantly lower amounts of soft drink/cordial compared to children who were overweight/obese at follow-up, further substantiating a role for soft drinks in excess weight gain. In contrast to findings from earlier studies, 6,7 increased sweetened beverage did not displace milk consumption in the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, children who were overweight/obese at baseline but had acceptable BMI at follow-up consumed significantly lower amounts of soft drink/cordial compared to children who were overweight/obese at follow-up, further substantiating a role for soft drinks in excess weight gain. In contrast to findings from earlier studies, 6,7 increased sweetened beverage did not displace milk consumption in the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…2 Regular consumption of fruits and vegetables was inversely associated with that of non-diet soft drinks, especially in females. A similar association was reported by Marshall et al 14 in U.S. children, by Figueiredo et al 9 in adults in São Paulo and in young adults in Japan. 23 In conclusion, the consumption of non-diet soft drinks in adults in Pelotas is high, especially among males, current smokers and those who eat snack foods every week and do not regularly consume fruits and vegetables.…”
Section: Discussionsupporting
confidence: 69%
“…Several studies have demonstrated that when milk is largely excluded from an adolescent's diet, it is difficult for him to achieve the daily requirements for calcium and other nutrients [52], [53] and [54]. Hence, consumption of the recommended amounts of milk may help adolescents meet their nutritional requirements and improve their diet quality [55] and [56]. It is important to note that the median amount reported in the appropriate categories of dairy consumption is consistent with current Portuguese recommendations for 2 to 3 servings of dairy products per day as part of a healthy diet [57].…”
Section: Discussionmentioning
confidence: 99%